Analysis of the Merdeka Curriculum in Enhancing Student Competencies in the Digital Era - Koko Adya Winata; Afeefa Binti Aminuddin; Hisny Fajrussalam (Didaktika: Jurnal Kependidikan, 2026)
The rapid development of digital technology has compelled the education sector to undertake curricular transformation in order to prepare students for the challenges of the twenty-first century. The Merdeka Curriculum has emerged as a strategic policy that emphasises learning flexibility, character development, and the strengthening of digital literacy competencies as essential prerequisites for navigating the modern era. This study aims to analyse the contribution of the Merdeka Curriculum to enhancing student competencies in the digital era. A qualitative approach with descriptive analysis is employed through library research methods, encompassing an in-depth review of relevant literature, analysis of official curriculum documents, and participatory observation of learning practices in the field as supporting secondary data. The findings indicate that the Merdeka Curriculum possesses strong potential to foster digital competencies, including critical thinking, creativity, collaboration, communication, and technological literacy skills. However, its effectiveness is highly dependent on teachers’ pedagogical readiness, the quality of instructional resources, the availability of technological infrastructure, and an adaptive school culture that embraces innovation. This study underscores the importance of strengthening teacher capacity, providing adequate digital facilities, and systematically integrating technology-based learning to ensure the optimal achievement of the Merdeka Curriculum’s objectives. These findings contribute to the development of educational policy and enrich scholarly discourse on the implementation of competency-based curricula in the digital era.